Large-scale dynamic optimization of a low density polyethylene plant - Cervantes, A. (2000)
This paper presents the optimal control policy of an industrial low-density polyethylene (LDPE) plant. Based on a dynamic model of the whole plant, optimal feed profiles are determined to minimize the transient states generated during the switching between different steady states. This industrial process produces LDPE by high-pressure polymerization of ethylene in a tubular reactor. The plant produces different final products. The model consists of two parts, the first one corresponds to the reactor and the second to the rest of the plant. The process has many time delays that are also incorporated into the optimization model. The resulting differential algebraic equation (DAE) plant model includes over 500 equations. The continuous state and control variables are discretized by applying orthogonal collocation on finite elements. The resulting NLP is solved with a reduced space interior point algorithm. The paper studies two cases of switching among different polymer grades determining the optimal butane flow rates, in order to minimize the time to reach the steady state operation corresponding to the desired new product quality.